'Immanent transcendence': Toward a genealogical analysis of a key concept in the philosophy of Mou Zongsan (1909–1995). Issue 2 (3rd April 2021) - Van den Stock, Ady
ABSTRACT: The aim of this paper is to offer a new interpretation of the controversial concept of 'immanent transcendence' ( neizai chaoyue 内在超越) in the work of the Confucian philosopher Mou Zongsan 牟宗三 (1909–1995). After a series of introductory remarks on the semantic and conceptual range of the terms 'immanence' and 'transcendence' in comparative philosophy,  I go on to provide a historically sensitive analysis of the origins of thenotion of 'immanent transcendence' in Mou's work. In doing so, I argue that rather than merely reflecting a blanket ontological or epistemological claim serving todifferentiate Chinese from Western culture and thought, the paradoxical concept of 'immanent transcendence' has a profoundly socio-political dimension and testifies Mou's efforts to maintain a form of continuity between the normative and the factual in the face of the unprecedented challenges faced by the Confucian tradition in the modern era.